2004
DOI: 10.1089/cbr.2004.19.443
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Therapeutic Tumor Response Using 99mTc-Ethylenedicysteine-Glucosamine

Abstract: Purpose: The aim of this study was to evaluate 99m Tc-ethylenedicysteine-glucosamine (EC-DG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Tc-glucosamine by labeling sterile glucosamine (AZPA International, Yantai Dongchong Biochemical Co. Ltd.; Shandong, China) using the method described by Yang et al (4,5) The radiochemical purity was >98%. A 400-MBq dose of 99m Tc-glucosamine (containing 1-2 mg glucosamine) in a bolus of 0.5 mL of normal saline was intravenously administered to each patient via a cannula using the vein in either cubital fossa over 15 s and was flushed with 0.9% normal saline.…”
Section: Radiochemists At Westmead Hospital Produced 99mentioning
confidence: 99%
“…Tc-glucosamine by labeling sterile glucosamine (AZPA International, Yantai Dongchong Biochemical Co. Ltd.; Shandong, China) using the method described by Yang et al (4,5) The radiochemical purity was >98%. A 400-MBq dose of 99m Tc-glucosamine (containing 1-2 mg glucosamine) in a bolus of 0.5 mL of normal saline was intravenously administered to each patient via a cannula using the vein in either cubital fossa over 15 s and was flushed with 0.9% normal saline.…”
Section: Radiochemists At Westmead Hospital Produced 99mentioning
confidence: 99%
“…These glucose membrane transporters are involved in both the glycolytic pathway and the hexosamine biosynthetic pathway. Cell cycle analysis revealed that 99m Tc-ECG was able to transport across the nucleus membrane and involved in proliferation activity in all phases cell cycles [14]. Moreover, the thymidine incorporation assay studies showed similar uptake patterns for both unlabeled ECG and glucose, suggesting that both ECG and glucose were involved in the proliferation/growth activity of cells, whereas unlabeled FDG was not [14].…”
Section: Discussionmentioning
confidence: 99%
“…Ethylenedicysteine (EC) is the most recent and successful example of N 2 S 2 chelates (1821). EC can be labeled with metallic isotopes easily and efficiently with high radiochemical purity and stability (1214).…”
Section: Discussionmentioning
confidence: 99%